Seismic vulnerability of URM structures based on a Discrete Macro-Element Modeling (DMEM) approach. (15th December 2019) - Chácara, César; Cannizzaro, Francesco; Pantò, Bartolomeo; Caliò, Ivo; Lourenço, Paulo B.
Highlights: A novel 3D macro-model is used to assess the seismic vulnerability of masonry structures. An alternative procedure for defining displacement capacity is presented. The seismic vulnerability assessment is performed through fragility curves and the application of nonlinear dynamic analyses. Abstract: The assessment of the seismic vulnerability of unreinforced masonry (URM) structures based on numerical modeling constitutes a difficult task due to their complex behavior, especially in the nonlinear dynamic field, and the lack of suitable, low-demanding, computational tools. In the last decades, practical statistical tools for the derivation of fragility curves have been successfully proposed mainly with reference to framed structures. This approach has been adopted also for the seismic vulnerability assessment of masonry buildings focusing on the in-plane collapse mechanisms by means of equivalent frame models. Nevertheless, the lack of computationally effective tools which involve the interaction between in-plane and out-of-plane mechanisms makes the definition of fragility curves an arduous task when it comes to existing masonry structures without box behavior. In this paper, a practical and thorough methodology for the assessment of the seismic vulnerability of URM buildings by means of analytical fragility curves is presented. This methodology presents some innovative features such as the definition of the Limit States (LSs) and their corresponding capacity based on multi-directional pushover analyses, as well as the application of nonlinear dynamic analyses, performed using a discrete macro-element modelling approach capable of simulating the main in-plane and out-of-plane responses of URM structures with a reduced computational burden. The present investigation focuses on the application of this methodology for assessing the seismic vulnerability of a brick masonry structure characterized by a strong out-of-plane failure mechanism. After a fitting process, the fragility curves were compared to the ones obtained using expert-based approaches.